The Role of Students in Improving the Quality of The Village Through Community Service Activities - Icha Fahriza; Ayu Juniaty Siregar; Aghna Ilmi Parinduri; Tisya Amalia Putri; Fitri Aisyah Amini Nst; Dea Nita Aulia; Nazwa Atalia Zahra; Milia Putri; Rina Zakiya; Idris Sadri (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Community service is an activity carried out by individuals or groups, where this task is given by lecturers in carrying out the TriDharma of Higher Education, namely the aspect of service. This community service is carried out to increase community awareness and activeness in forming and developing villages. This research shows the role of students in making it happen. This activity involves efforts such as "Anti-bullying" socialization education for students, mutual cooperation, teaching ngaji at the Qur'an house, and environmental awareness efforts. Community service by students can be the first step in renewing the quality of life of a village and society. This research emphasizes the importance of the active role of students in building villages and providing recommendations for the implementation of similar programs in the future